Potato Physiological Disorders - Brown Center and Hollow Heart - Chad M. Hutchinson (EDIS)
Brown center and hollow heart are physiological disorders of the potato tuber. Brown center is characterized by a region of cell death in the pith of the tuber which results in brown tissue. Hollow heart is characterized by a star shape hollow in the center of the tuber. Brown center frequently precedes the development of hollow heart. Neither disorder is initiated by a disease organism. This document is HS945, one of a series of the Horticultural Sciences Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date: August 2003.